R Representasi Maskulinitas Pada Tokoh Dola dalam Anime Laputa: Castle in the Sky (1986) - Kadek Dian Dewi; Kadek Eva Krishna Adnyani; Yeni Yeni (Journal Social and Humaniora, 2024)
This research aims to describe the representation of masculinity in the Dola character in the anime "Laputa: Castle in the Sky (1986)." This study is a linguistic research employing a qualitative descriptive method. The research theory used includes Roland Barthes' semiotics and the concept of masculinity by David Deborah and Robert Brannon. Data collection was conducted through observation and note-taking, and data validity was ensured through data triangulation. The findings of this study indicate that the character Dola reflects masculinity. Various signs of masculinity are evident through Dola's character design, which includes dominance, protectiveness, the ability to separate feelings from ideas, aggressiveness, ambition, physical strength, rationality, leadership qualities, daringness, competence and competitiveness. Despite embodying masculinity, Dola maintains feminine aspects in her appearance, as reflected in her wearing of a skirt, two braided pink hair, the use of earrings, and her tender-heartedness displayed through her affection for Sheeta and Pazu.